657 ROUTINE ESOPHAGRAMS FOLLOWING HIATUS HERNIA REPAIR MINIMISES REOPERATIVE MORBIDITY: A MULTICENTER COMPARATIVE COHORT STUDY. (17th September 2021) - Liu, David; Wee, Melissa; Grantham, James; Ong, Bee; Ng, Stephanie; To, Minh-Son; Zhou, Xuanyu; Irvine, Tanya; Bright, Tim; Thompson, Sarah; Dandie, Lachlan; Shenfine, Jonathan; et al.
Abstract:  : Hiatus hernia repairs are common. Early complications such as re-herniation, esophageal obstruction and perforation, although infrequent, incur significant morbidity. Here, we determine whether routine postoperative esophagrams following hiatus hernia repair may expedite the surgical management of these complications, reduce reoperative morbidity, and improve functional outcomes. Methods: Analysis of a prospectively-maintained database of 1829 hiatus hernia repairs undertaken in 14 hospitals from 1 January 2000 to 30 September 2020. 1571 (85.9%) patients underwent a postoperative esophagram which was reviewed. An early (<14 days) reoperation was performed in 44 (2.4%) patients. Results: Compared to those without an esophagram, patients who received one prior to reoperation (n = 37) had a shorter time to diagnosis (2.4 vs. 3.9 days, p = 0.041) and treatment (2.4 vs. 4.3 days, p = 0.037) of their complications. This was associated with decreased open surgery (10.8% vs. 42.9%, p = 0.034), gastric resection (0.0% vs. 28.6%, p = 0.022), postoperative morbidity (13.5% vs. 85.7%, p < 0.001), ICU admission (16.2% vs. 85.7%, p < 0.001), and length-of-stay (7.3 vs. 18.3 days, p = 0.009). Furthermore, patients who underwent early reoperations for asymptomatic re-herniation had less complications and superior functional outcomes at one-year follow-up than those who needed surgery for symptomatic recurrences later on. Conclusion: Postoperative esophagrams decreases the morbidity associated with early and late reoperations following hiatus hernia repair, and should be considered for routine use.